Standardized evaluation of satisfaction within urology residents during clinical training: Implementation of a new urological residency rotation program at the university hospital Frankfurt - Siech, Carolin; García, Cristina Cano; Leyh, Herbert; Schmid, Hans-Peter; Engl, Tobias A; Karakiewicz, Pierre I; Becker, Andreas; Chun, Felix K-H; Banek, Séverine; Kluth, Luis A (Frontiers in Surgery, 2022)
Background Structured curricula are demanded to improve training programs of future urologists. This study aimed to evaluate the acceptance of the newly implemented residency rotation program at the University Hospital Frankfurt. Primary endpoint was resident’s satisfaction with the current residency rotation program. Secondary endpoint was the fulfilment of the objectives and expectations by residents. Methods A standardized 15-item, online-based survey was sent to every urologic resident of the University Hospital Frankfurt, completing their rotation between August 2020 and August 2022. In addition to baseline characteristics, training and working conditions were assessed. Descriptive statistics were applied. Results In total 15 rotations of the Residency Rotation Program at the University Hospital Frankfurt were evaluated, including urologic practice (5/15), Intermediate Care Unit (4/15), urooncology (4/15) and clinical exchange to St. Gallen (2/15). Overall, the majority were very (67%) or rather satisfied (2 %) with their rotation. Of the pre-rotation defined objectives, 71% were fulfilled, 18% partially fulfilled and 8% not fulfilled. With respect to the expectations, 67% were fulfilled, 19% partly fulfilled and 4% were not fulfilled. All residents would recommend their respective rotations. Conclusion Our results demonstrate that the residency rotation program at the University Hospital Frankfurt enjoys a high level of acceptance as well as a positive impact on urologic training. Satisfaction with the completed rotation was convincing, most of the expectations and objectives for the respective rotation could be fulfilled. These results help to ensure the quality of urologic curricula and to improve the structure of training programs for future urologists.